The no-end house - Bates, Jeremy (Kensington Publishing Corp., 2025)
Haunted by his wife's death, Joe Hadfield enters a notorious escape-room challenge in Barcelona's Gothic Quarter, where nine terrifying rooms prey on his fears, forcing him to confront his past and uncover the sinister secrets of The No-End House before it consumes him entirely.